Witnessing the Shared Story of Intergenerational Trauma in a Chinese Canadian Family: An Autoethnographic Narrative - Chou, Fred; Huang, Carmen (Canadian Journal of Counselling and Psychotherapy, 2024)
This article presents the narrative of the first author witnessing the process of sharing intergenerational trauma (IGT) stories between a parent-offspring dyad. The narrative described in this paper is part of a study that involved the construction of IGT narratives in Chinese Canadian families (Chou et al., 2023). Arvay’s (2003) Collaborative Narrative Method was utilized to develop participant narratives, while autoethnographic data was used to construct the researcher’s narrative. The paper introduces an intergenerational family dyad (father-daughter) engaging in a facilitated process that involved sharing their IGT stories with one another and presented from the researcher’s perspective. The study has implications for researchers and practitioners working with IGT in the Chinese diasporic community as well as other ethnocultural groups. It provides insight into a scarcely studied phenomenon and illustrates how IGT narratives can be shared in a facilitated and supportive manner and has implications for research and clinical practice.